Pengaruh Service Excellence, Promosi, Dan Variasi Produk Terhadap Kepuasan Pelanggan Jelita Cosmetics (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Wijaya Kusuma Surabaya) - Ramadhan, Rahmat Hidayatullah; Trimarjono, Adrianto (PRAGMATIS, 2025)
This research aims to analyze the influence of service excellence, promotions and product variations on customer satisfaction at Jelita Cosmetics, with a case study of students at the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. The research method used is quantitative by collecting data through questionnaires and literature study. The research population is active students of the Faculty of Economics and Business, Wijaya Kusuma University who are customers of Jelita Cosmetics, with a sample of 75 respondents selected using a simple random sampling technique. Data analysis was carried out using multiple linear regression, classical assumption tests, as well as t tests and f tests for hypothesis testing. The research results show that the three independent variables, namely service excellence, promotion and product variety, have a positive and significant effect on customer satisfaction. Service excellence contributes through friendly, responsive and professional service, while promotion influences customer perceptions and purchasing decisions through strategy. interesting things such as discounts and loyalty programs. Product variety plays an important role in meeting customer needs by providing diverse product choices according to preferences.